Strategi Manajemen Sumberdaya Manusia Dalam Mencapai Keunggulan Bersaing Pada Era Globalisasi - Muhamad Juaini; Muhammad Rapii (Educatio, 2017)
Global competition marked by the emergence of many competitors operating in the world and the emerging markets of competitors in other countries led to the business environment into a dynamic and strong competition. With qualitative research is research that aims to understand the phenomenon of what is experienced by research subjects holistically, and by way of description in the form of words and languag, in a specific context by using various natural and scientific methods. Collecting technique is interview and documentation study. Data collection methods used in this study include, the method of interviews and documentation methods The results show that is expected to coordinate all organizational elements to be managed jointly with the hope of improving the performance of the organization concerned